2007
DOI: 10.1186/1745-6150-2-33
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of orthologous genes for 41 archaeal genomes and implications for evolutionary genomics of archaea

Abstract: Background: An evolutionary classification of genes from sequenced genomes that distinguishes between orthologs and paralogs is indispensable for genome annotation and evolutionary reconstruction. Shortly after multiple genome sequences of bacteria, archaea, and unicellular eukaryotes became available, an attempt on such a classification was implemented in Clusters of Orthologous Groups of proteins (COGs). Rapid accumulation of genome sequences creates opportunities for refining COGs but also represents a chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
192
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(212 citation statements)
references
References 81 publications
(62 reference statements)
16
192
1
Order By: Relevance
“…No unambiguous origin of replication could be determined on the basis of local gene content or GC skew, as commonly observed for other archaeal genomes (14). Approximately 61% of the N. maritimus open-reading frames (ORFs) could be assigned to clusters of orthologous groups of proteins (COGs), a lower percentage than for genomes of ammonia-oxidizing bacteria (AOB) ( Table S1) but similar to Cenarchaeum symbiosum (15). The genome possesses a relatively high coding density (91.9%), with a larger fraction dedicated to energy production/conservation, coenzyme transport/metabolism, and translation genes than other characterized Crenarchaeota, but similar to two common species of photoautotrophic marine Bacteria, Prochlorococcus, and Synechococcus.…”
Section: Resultsmentioning
confidence: 99%
“…No unambiguous origin of replication could be determined on the basis of local gene content or GC skew, as commonly observed for other archaeal genomes (14). Approximately 61% of the N. maritimus open-reading frames (ORFs) could be assigned to clusters of orthologous groups of proteins (COGs), a lower percentage than for genomes of ammonia-oxidizing bacteria (AOB) ( Table S1) but similar to Cenarchaeum symbiosum (15). The genome possesses a relatively high coding density (91.9%), with a larger fraction dedicated to energy production/conservation, coenzyme transport/metabolism, and translation genes than other characterized Crenarchaeota, but similar to two common species of photoautotrophic marine Bacteria, Prochlorococcus, and Synechococcus.…”
Section: Resultsmentioning
confidence: 99%
“…The applied gel-and enrichment-free PAcIFIC (precursor acquisition independent from ion count) approach (438) revealed an unexpectedly large number of phosphoproteins (540 phosphoproteins) as well as a large amount of p-Tyr (54%) (439). The identified phosphoproteins are located in 21 out of 26 arCOG categories (440), indicating that most of the cellular processes are targeted by protein phosphorylation. For Sul.…”
Section: Regulation At the Protein Levelmentioning
confidence: 99%
“…Furthermore, the identified percent pS/T/Y ratio is unique regarding the amount of p-Tyr (54%) compared to those reported for other phosphoproteome studies (1 to 10%). It was shown that the identified phosphoproteins are located in 21 out of 26 arCOG categories (440), indicating that most of the cellular processes are targeted by protein phosphorylation. In response to the offered carbon source, significant changes in the complex phosphorylation pattern were observed, suggesting an important physiological function of reversible protein phosphorylation in the control of central carbohydrate metabolism.…”
Section: Sulfolobus Solfataricusmentioning
confidence: 99%
“…The increasing availability of sequence information from diverse organisms has allowed the application of comparative genomics, or phylogenomics, to discover proteins specific to bacteria (10 -12), cyanobacteria (13)(14)(15), fungi (16,17), metazoa (18), archaea (19), and plastids (20). Additionally, computational attempts have been made to recognize protein families that are conserved in select plant genomes (21).…”
mentioning
confidence: 99%